Pembinaan Anak Jalanan Melalui Rumah Singgah Holi Di Kelurahan Tanjung Hilir Kecamatan Pontianak Utara - Daniel, Stefanus (UNIVERSITAS TANJUNGPURA, 2014)
This study aims to describe the development of street children, how its implementation, development activities as well as constraints during the development of street children from Holi halfway house Kel. Tanjung Hilir, Kec. Pontianak Utara. The method used is descriptive method with qualitative approach with the goal of researchers can learn more about the role of Holi halfway house. The results showed that the coaching street children in Holi halfway house focused on fostering educational, spiritual and social. Direct spiritual guidance to shape the behavior of the child in accordance with religious norms. Coaching aims discipline children early so that children have mental self-discipline and discipline time. Aimed at fostering social relationships so that children can have a good relationship between the members in the social environment. Coaching hygiene for children to know the importance of target children clean and healthy living.Â Keywords : Fostering, Street Children, Halfway House, Qualitative.